PENGARUH MEDIA PEMBELAJARAN AUDIO VISUAL TERHADAP HASIL BELAJAR GEOGRAFI KELAS X FASE E DI SMA N 2 PAYAKUMBUH - aji cha chaniago; Syafri Anwar (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
The purpose of this study is to investigate how the use of audio-visual learning materials affects the geography learning outcomes of SMA N 2 Payakumbuh's class X Phase E pupils. The approach was a two-group experiment using audio-visual media in the experimental group and traditional methods in the control group. Tests of learning outcomes are used to gather data both before and after instruction. According to the analysis's findings, pupils who were taught with audio-visual materials scored noticeably higher than those who were taught through traditional means. According to these results, students' comprehension of geographic ideas and engagement with the learning process can both be improved by using audio-visual learning materials. Consequently, it is advised that educators use audiovisual materials into their lessons to raise the caliber of geography learning in schools.